Refractory Polyradiculoneuritis Responsive to Cyclophosphamide: A Case Report of a Patient with a History of Diffuse Large B Cell Lymphoma and CAR-T Cell Therapy - Kreb, Luisa; Uceyler, Nurcan; Schindehutte, Magnus; Geis, Christian; Tumani, Hayrettin; Sommer, Claudia; Haeusler., Karl Georg (Archives of Clinical and Medical Case Reports, 2026)
Background: Polyradiculoneuritis is a rare but serious neurological condition with diverse etiologies, including autoimmune, paraneoplastic, and therapy-induced mechanisms. In oncologic patients, particularly those with hematologic malignancies and prior immune-directed therapies, diagnosis and treatment can be especially challenging. Case presentation: We report on a 69-year-old woman with acute onset and rapid progression of a polyradiculoneuritis with a history of B-cell lymphoma and chimeric antigen receptor (CAR)-T cell therapy. While response to standard glucocorticoid, intravenous immunoglobulin, or plasma exchange was insufficient, the patient was successfully treated with cyclophosphamide (CYC). Conclusions: This case highlights the importance of considering autoimmune polyradiculoneuritis in immunotherapy-exposed patients with rapidly progressive neuropathy. When first-line treatments fail, and histopathology shows T-cell predominance, CYC may be an effective therapeutic option.